2007
DOI: 10.1242/dev.02797
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of smoothened (SMO) in mammary glands of transgenic mice leads to increased proliferation, altered differentiation and ductal dysplasia

Abstract: The hedgehog signaling network regulates pattern formation, proliferation, cell fate and stem/progenitor cell self-renewal in many organs. Altered hedgehog signaling is implicated in 20-25% of all cancers, including breast cancer. We demonstrated previously that heterozygous disruption of the gene encoding the patched-1 (PTCH1) hedgehog receptor, a negative regulator of smoothened (Smo) in the absence of ligand, led to mammary ductal dysplasia in virgin mice. We now show that expression of activated human SMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
213
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(221 citation statements)
references
References 46 publications
6
213
1
1
Order By: Relevance
“…49 Furthermore, in samples from human breast cancer patients, cells with deregulated Hh activity did not label for the proliferation marker Ki67, implying a non-cell autonomous effect of deregulated Hh signaling. 50 Although these studies focused on proliferation, we demonstrate here that deregulated Hh signaling also increases resistance to apoptosis non-cell autonomously.…”
Section: Discussionmentioning
confidence: 62%
“…49 Furthermore, in samples from human breast cancer patients, cells with deregulated Hh activity did not label for the proliferation marker Ki67, implying a non-cell autonomous effect of deregulated Hh signaling. 50 Although these studies focused on proliferation, we demonstrate here that deregulated Hh signaling also increases resistance to apoptosis non-cell autonomously.…”
Section: Discussionmentioning
confidence: 62%
“…Studies from the neural field have demonstrated that neurosphere formation overestimates stem cell frequency (by about 30-50-fold) and that all but the largest neurospheres are derived from non-stem progenitor cells [34,35]. A similar phenomenon appears to be occurring when mammary cells are placed into culture, since transplantation of individual mouse-derived mammospheres into cleared mammary fat pads results in only a 15% engraftment success rate [36]. Unfortunately, it is not clear at this point which cells in the mammary epithelial cell hierarchy can function as mammosphere-initiating cells.…”
Section: Mammosphere Assaysmentioning
confidence: 99%
“…These frequencies have ranged widely from 1 MRU in 100 total cells to <1 in 4900 cells [9,16,18,36]. Presumably this large variation is due to the different methods used to dissociate the mammary tissue and to transplant the cells; however, it is not known whether these different dissociation and transplantation protocols are liberating different functional classes of MRUs.…”
Section: In Vivo Models To Detect Mouse Mascsmentioning
confidence: 99%
“…Gli1 itself may induce early osteoblast differentiation in a Runx2-independent manner and play key roles with Gli2 and Gli3 in osteogenesis (Hojo et al, 2012). Shh signaling is also involved in tumorigenesis in several cancers, particularly in breast cancers (Moraes et al, 2007). Because of this, considerable interest in elucidating the cellular and molecular mechanisms involved in Smo-mediated signaling has recently emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Smo is also frequently and ectopically expressed in human breast cancers (Visbal et al, 2011), while altered hedgehog signaling is implicated in approximately 20-25% of all cancers (Briscoe and Therond, 2005). Considerable evidence has shown that sustained Smo-mediated activation of hedgehog signaling leads to increased proliferation and abnormal ductal morphology of the mammary gland, although Smo activation in luminal mammary epithelial cells was found only in a small percentage (-5%) of glands (Moraes et al, 2007). It was also suggested that Smo stimulates proliferation via a non-cell autonomous paracrine or juxtacrine mechanism (Visbal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%